Evaluating transnational NGOs : legitimacy, accountability, representation - Steffek, Jens.; Hahn, Kristina, 1975- (Houndmills, Balsingstoke, Hampshire [England] ; Palgrave MacMillan, 2010)
'This book provides the reader with a broad overview of the current debate on the evaluation of transnational NGOs, combining the academic with the practitioners perspectives. The contributions to this edited volume deal with the key concepts of legitimacy, accountability and representation, covering a variety of issue areas and NGOs'--Provided by publisher.
Machine generated contents note: Introduction: Transnational NGOs and Legitimacy, Accountability, Representation--J.Steffek &--K.Hahn -- PART I: NGO LEGITIMACY -- The Debate on NGOs Legitimacy: What Can we Learn from the Classics?--L.Schrader &--T.Denskus -- Legitimating INGO Advocacy: The Case of Internal Democracies--D.Halpin &--P.Mc Laverty -- The Link between Standard-Setting NGOs Legitimacy and Effectiveness: An Exploration of Social Mechanisms--M.Beisheim &--K.Dingwerth -- Assessing the Democratic Legitimacy of Transnational NGOs: Five Criteria--J.Steffek, R.Bendrath, S.Dalferth, K.Hahn, M.Piewitt &--M.Rodekamp -- PART II: NGO ACCOUNTABILITY -- These Pages have been Regulated for You: Issues Arising from the Governance of Markets by NGOs--J.Bendell, P.Jay &--M.Bendell -- Accountability 2.0: In Search for a New Approach to International Non-Governmental Organizations Accountability--M.Havrda &--P.Kutilek -- PART III: REPRESENTATION THROUGH NGOS? -- Representing the People? NGOs in International Negotiations--T.Brhl -- Regulating NGO Participation in the EU--A De-Facto Accreditation System Built on Representativeness?--J.Greenwood -- NGOs Power of Advocacy: The Construction of Identities in UN Counter-Human Trafficking Policies--K.Hahn -- PART IV: CONCLUSIONS -- Evaluating NGOs: A Practitioners Perspective--R.Heggli -- Evaluating NGOs: Prospects for Academic Analysis--J.Steffek &--K.Hahn.
Includes bibliographical references and index.
Keywords: Non-governmental organizations; International agencies